Onomatope dalam Istilah-istilah Gamelan Jawa - Kristi, Tania; Hendrokumoro, Hendrokumoro (Arnawa, 2023)
Onomatopoeia in Javanese is attached to the Javanese musical art activity called gamelan or Karawitan. Just as music is related to sounds, there are various gamelan terms which are onomatopoeia. The lack of research on the onomatopoeia of these terms motivated a preliminary study of how onomatopoeia is formed in Javanese gamelan terms and its use in both verbal and written. Data was taken from literature studies and independent reflection based on the author's observation experiences. Next, the data is classified based on word form and the use of terms in gamelan practice. This research found onomatopoeia in Javanese gamelan terms which are dominated by secondary forms of onomatopoeia, namely imitations of sounds from the gamelan instruments being played. Meanwhile, based on word formation, onomatopoeia of gamelan terms consists of (1) root words as basic words, (2) root words plus formative, (3) root words doubled, (4) two or more root words, and (5) compound words. Based on their use, these terms are divided into four functions, namely as a basis for naming gamelan instruments, naming gamelan percussion techniques, and to describe gamelan sounds. The use of these terms can also be seen verbally and written. === Onomatope dalam bahasa Jawa melekat pada aktivitas seni musik Jawa yang disebut dengan gamelan atau seni karawitan. Sebagaimana musik berhubungan dengan suara dan bunyi-bunyian, ada berbagai istilah gamelan yang merupakan bentuk onomatope. Minimnya penelitian tentang onomatope istilah-istilah tersebut memotivasi kajian awal terhadap pembentukan onomatope dalam istilah gamelan Jawa dan fungsi atau penggunaannya baik secara tertulis maupun secara verbal. Data diambil dari studi literatur dan refleksi mandiri berdasarkan pengalaman observasi penulis. Berikutnya, data diklasifikasikan berdasarkan pembentukan kata dan penggunaan istilah-istilah dalam praktik gamelan. Penelitian ini menemukan jenis onomatope dalam istilah-istilah gamelan Jawa yang didominasi bentuk onomatope sekunder, yaitu tiruan-tiruan bunyi dari instrumen gamelan yang dimainkan. Sementara itu, berdasarkan pembentukan katanya, onomatope istilah-istilah gamelan terdiri dari (1) akar kata sebagai kata dasar, (2) akar kata ditambah formatif, (3) akar kata diduakalikan, (4) dua akar kata atau lebih, dan (5) kata majemuk. Berdasarkan penggunaannya, istilah-istilah ini terbagi dalam empat fungsi yaitu sebagai dasar penamaan instrumen gamelan, penamaan teknik tabuh gamelan, dan untuk mendeskripsikan bunyi gamelan. Penggunaan istilah-istilah ini juga dapat dilihat secara lisan dan tertulis.